From anthropocentric to ecocentric jurisprudence: A maqasid-based reconstruction of Islamic environmental ethics toward intergenerational equity - Achmad Alfan Kurniawan; Istiqomah Fadlillah (Al'Adalah, 2025)
Contemporary ecological crises, including climate change, pollution, ecosystem degradation, water scarcity, and biodiversity loss, reveal that environmental damage is not merely a technical problem of resource management, but also an ethical, legal, and intergenerational concern. Existing studies on Islamic environmental ethics have developed through three main trajectories: moral-theological discussions of tawhid, khalifah, amanah, and mizan; eco-maqasid approaches that connect environmental protection with Islamic legal philosophy; and sustainability-oriented studies addressing biodiversity, bioethics, and future generations. However, these trajectories remain insufficiently integrated into a unified jurisprudential framework that links Islamic environmental ethics, maqasid al-shariah, and intergenerational equity. This article aims to reconstruct Islamic environmental ethics from anthropocentric-instrumental tendencies towards an ecocentric-oriented maqasid jurisprudence. Employing a normative-conceptual method through philosophical, maqasidi, and environmental ethical approaches, the article argues for a shift from human-centred maslahah to life-system-centred maslahah. The findings show that ecological integrity is not an additional object of sharia protection, but a structural prerequisite for the realisation of protection of religion, life, intellect, progeny, and property (al-dharuriyyat). The article concludes that ecocentric-oriented maqasid jurisprudence provides a normative framework for ecological justice, intergenerational responsibility, environmental fiqh, ecological fatwas, and maqasid-based public policy.